Film-Forming Systems for Dermal Drug Delivery - Pünnel, Larissa Carine (Pharmaceutics, 2021)
Film-forming formulations represent a novel form of sustained release dermatic products. They are applied to the skin as a liquid or semi-solid preparation. By evaporation of the volatile solvent on the skin, the polymer contained in the formulation forms a solid film. Various film-forming formulations were tested for their water and abrasion resistance and compared with conventional semi-solid formulations. Penetration and permeation studies of the formulations indicate a potential utility as transdermal therapeutic systems. They can be used as an alternative to patch systems to administer a variety of drugs in a topical way and may provide sustained release characteristics.